Non-heteronormative sexual orientations at work: Disclosure dynamics and the negotiation of boundaries between lesbian and gay employees and their co-workers - Di Marco, D.; Hoel, H.; Arenas, A.; Munduate, L. (Journal of Homosexuality, 2024)
This article focuses on the interactional dynamics which take place during disclosure of non-heteronormative sexual orientations at work. Since the disclosure might be considered a process through which lesbian and gay (LG) people share information about their personal life at work, Boundary Theory, which explores how people create boundaries between life domains, allows us to better understand disclosure dynamics. For this purpose, 39 Spanish lesbian and gay employees were interviewed. The results demonstrated that LG employees and their coworkers, affected by the socio-cultural context, are jointly responsible for the integration/segmentation of LG employees’ personal and work domains, thus questioning the extent to which management of non-heteronormative sexual orientations is considered a strategic choice under the control of LG employees alone.